Oral supplementation with branched‐chain amino acid granules prevents hepatocarcinogenesis in patients with hepatitis C‐related cirrhosis: A propensity score analysis. Issue 3 (29th April 2013) - Tada, Toshifumi; Kumada, Takashi; Toyoda, Hidenori; Kiriyama, Seiki; Tanikawa, Makoto; Hisanaga, Yasuhiro; Kanamori, Akira; Kitabatake, Shusuke; Niinomi, Takuro; Ito, Takanori; Hasegawa, Ryohei; Ando, Yusuke; et al.
<x xml:space="preserve">Abstract</x> Aim It has been reported that branched‐chain amino acids (BCAA) supplementation can improve nutritional status and reduce liver‐related complications in patients with decompensated cirrhosis. BCAA supplementation reportedly reduces the incidence of hepatocellular carcinoma (HCC) in obese cirrhotic patients infected with hepatitis C virus (HCV). We investigated the effects of oral supplementation with BCAA granules on hepatocarcinogenesis in patients with HCV‐related cirrhosis using propensity score matching. Methods A total of 60 patients with HCV‐related cirrhosis and without history of HCC who were selected by one‐to‐one matching of propensity scores: 30 patients receiving 12 g/day of BCAA granules for 3 months or more (BCAA group) and 30 being observed without BCAA supplementation (control group). The impact of BCAA supplementation was analyzed on the incidence of HCC. Results The 3‐ and 5‐year rates of HCC development were 13.7% and 13.7% in the BCAA group and 35.1% and 44.5% in the control group, respectively. The BCAA group had a significantly lower rate of HCC than the control group (P = 0.032). Multivariate analysis for factors that were associated with hepatocarcinogenesis indicated that BCAA supplementation was independently associated with a reduced incidence of HCC (hazard ratio 0.131; 95% confidence interval, 0.032–0.530; P = 0.004) along with sex and serum α‐fetoprotein. Obesity (body mass index, ≥25 kg/m2) was not significantly associated with an increased incidence of HCC. Conclusion Oral supplementation with BCAA granules is associated with a reduced incidence of HCC in patients with HCV‐related cirrhosis regardless of the presence of obesity based on the propensity score analysis.